2011
DOI: 10.1177/193229681100500328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes Mellitus on Outcomes of Hyperglycemia in a Mixed Medical Surgical Intensive Care Unit

Abstract: The results showed that a diagnosis of diabetes was not an independent predictor of mortality, and that diabetic patients who were uncontrolled did not have worse outcomes. Diabetic nonsurvivors were associated with a greater amount of hypoglycemic episodes, suggesting these patients may benefit from a more lenient blood glucose protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…We have previously shown that patients with a history of diabetes mellitus whose blood glucose was poorly controlled were not associated with an increased mortality; however, these patients demonstrated a significant intolerance to hypoglycemia. Diabetic patients with only one episode of a blood glucose <60 mg/dL were associated with a significant increase in adjusted mortality [8]. This finding may be associated with non-biologic reasons previously published, to include more attentive care by providers, appropriate treatment of other comorbidities, healthier life style recommendations provided by counseling as an outpatient, and potentially earlier admission to the hospital [7].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We have previously shown that patients with a history of diabetes mellitus whose blood glucose was poorly controlled were not associated with an increased mortality; however, these patients demonstrated a significant intolerance to hypoglycemia. Diabetic patients with only one episode of a blood glucose <60 mg/dL were associated with a significant increase in adjusted mortality [8]. This finding may be associated with non-biologic reasons previously published, to include more attentive care by providers, appropriate treatment of other comorbidities, healthier life style recommendations provided by counseling as an outpatient, and potentially earlier admission to the hospital [7].…”
Section: Discussionmentioning
confidence: 68%
“…There have been previous studies describing diabetes as a risk modifier during acute illness, where hyperglycemia in these patients may have a different biological and/or clinical implication, possibly due to the chronic nature of their disease and the ability to adapt to episodes of significant and sometimes long term hyperglycemia [7,8,27]. We have previously shown that patients with a history of diabetes mellitus whose blood glucose was poorly controlled were not associated with an increased mortality; however, these patients demonstrated a significant intolerance to hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some further interest in continuous glucose monitoring and, with better technology, options for this interesting development appear to be emerging [75]. Recent work suggests that diabetes mellitus does not increase mortality but may indeed improve outcome from a critical illness, thus confounding further the issue of the potential benefit from IIT [76].…”
Section: Glucosementioning
confidence: 97%
“…Blood or serum lactate measurements are of comparative specific value in the management of conditions such as congenital organic acidaemias, some toxic states (e.g. alcohols), although there can be analytical interference with some alcohols and POCT lactate measurements [76], as well as some infective conditions, most notably severe falciparum malaria [78][79][80]. Nevertheless, most of these acidotic states with multiple organ failure are accompanied by increased unmeasured anions that may be quantified using a calculation of the strong ion gap (SIG) [81].…”
Section: Lactatementioning
confidence: 99%